The rnam thar and mgur ʼbum of ʼBaʼ-ra-ba : with his Sgrub pa ñams su blaṅ baʼi lag len dgos ʼdod ʼbyuṅ baʼi gter mdzod - ʼBaʼ-ra-ba Rgyal-mtshan-dpal-bzaṅ-po, 1310-1391 (Urgyan Dorje, 1976)
Autobiography and songs of esoteric realization of the founder of the Barawa subsect of the Drukpa Kargyudpa tradition; includes his work on sadhana in Buddhism.